Traditional Myth and Culture Tourism in Bali - IGAO Mahagangga; Agung Suryawan Wiranatha; I Nyoman Sunarta; I Putu Anom (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
Cultural tourism in Bali has begun to be forgotten, despite the fact that the first arrival of tourists in the past was driven by a unique culture, an exotic community, and a way of life different from their origins, including traditional myths or local myths. This qualitative research focuses on understanding traditional myths as cultural capital in tourism and whether they still hold power in tourism development, especially through tour guides at tourist destinations through focus observations, in-depth interviews, and literature studies. The research results indicate that at present, cultural tourism has become a symbol with minimal practice in tourism products. The existence of Balinese traditional myths in tourism is threatened by tourism practitioners, such as tour guides, who simply follow market trends and believe that many tourists no longer appreciate traditional myths as they once did. There is a need to raise awareness and return cultural tourism to its roots through traditional myths. The role of local government and other tourism stakeholders is urgent and crucial. In addition, for the younger generation, traditional myths, which contain many hidden moral messages, will be useful for sustainable tourism development. This makes it possible to develop tourism without building splendor and dense infrastructure, but rather by optimizing the traditional myths that already exist throughout Bali.